Does Solo Self-Employment Serve as a 'Stepping Stone' to Employership? - Michael Leith Cowling; Mark Wooden (Institute of Labor Economics (IZA), 2019)
This paper examines the extent to which solo self-employment serves as a vehicle for job creation. Using panel data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, a dynamic multinomial logit model of transitions between labour market states is estimated. The empirical strategy closely follows that used in a previous study employing household data from Germany by Lechmann and Wunder (2017). Estimates of true cross-state dependence between solo self-employment and employership are obtained that are relatively small. Further, our results imply that the probability of a male remaining an employer just two years after transitioning out of solo self-employment is only 2% (and among women, it is virtually zero). The extent of both true cross-state dependence and true state dependence in employership is, however, much greater among individuals who have demonstrated a preference for self-employment in the past. This implies that pro-entrepreneurial policies that target more 'entrepreneurial' individuals will have more pronounced and long-term effects in stimulating job creation.
Keywords: L26; 330; dynamic multinomial logit; HILDA Survey; solo self-employment; state dependence; stepping stones